Effect of Applying Binocular Visual Training after Slanted Lateral Rectus Recession on Orthophoric Rate and Binocular Visual Function Recovery on Patients with Convergence Insufficiency-Type Intermittent Exotropia. (16th October 2021) - Dai, Shuying; Sun, Weifeng; Xu, Hongjia; Wang, Yanan; Liu, Yuan; Han, Aijun; Han, Lixiao; Wang, Juan; Liao, Rujuan; Liu, Sujiang; Gao, Yu; Han, Huifang
Abstract : Objective . To explore the effect of applying binocular visual training after slanted lateral rectus recession on orthophoric rate and binocular visual function recovery on patients with convergence insufficiency-type intermittent exotropia (CI-IXT). Methods . A total of 76 CI-IXT child patients treated at the Strabismus and Pediatric Ophthalmology Department of our hospital from June 2019 to June 2020 were selected as the research objects, and those who met the inclusion criteria were equally divided into group A (63 eyes) and group B (61 eyes) according to the sealed envelope randomization. All child patients accepted the slanted lateral rectus recession, and after that, those in group A accepted the binocular visual training and those in group B accepted the conventional visual function rehabilitation training, so as to compare their position of eye, the best corrected visual acuity, etc., after training for statistical analysis. Results . Compared with group B after one month of surgery, group A had significantly less patients with grade I binocular vision function (P  < 0.001) and more patients with grade II and III vision function (P  < 0.05); between group A and group B, after 3 months and 6 months of treatment, the number of eyes with normal stereoscopic vision was significantly higher in group A (P  < 0.05); at 15 days, 1 month, 3 months, and 6 months of treatment, the visual strain scores of group A were significantly lower (P  < 0.001); after treatment, the number of orthophoria eyes was significantly higher in group A (P  < 0.001), while the numbers of overcorrected eyes and undercorrected eyes were significantly higher in group B (P  < 0.001); and the total incidence rate of adverse reactions was significantly lower in group A (P  < 0.05). Conclusion . Applying binocular visual training to child patients with CI-IXT after slanted lateral rectus recession can promote the recovery of binocular vision and ensure higher safety, and further study will help to establish a better solution for the affected children.